Financial Performance Analysis of Public Enterprises (PEs) in Nepal - Poudel, Surya Prasad (Voice of Teacher, 2023)
The main objective of this study was to analyze the financial performance of Public Enterprises in Nepal. PEs in Nepal was incorporated for socio economic development of the country. There has been found 44 PEs in Nepal currently some of them incurred loss. On the basis of these, it is argued that financial performance of PEs in Nepal is weak. This study was carried out on the helps of trend analysis, profitability ratio and turnover ratio. Twelve years financial data were taken from publications of Ministry of Finance, Nepal Government and research articles, etc. All the secondary data were analyzed on quantitative approach with descriptive methods. The analysis showed revenue increased slowly on the basis of base year 2010/011 in 12 years. Similarly profit has found fluctuate over the study period between-0.524 to 7.323 times of base year profit 2010/011. The net profit margin ratio and return on shareholders’ net worth has not found satisfactory level. Total assets and net fixed assets turnover ratio have shown poor performance in assets utilization of PEs Nepal. The turnover ratio massaged that, there is a chances of enhancing financial performance of PEs Nepal by proper utilization of assets for inducing profitability position of PEs. The management of PEs should enhanced the financial performance of organization by the helps of budget as a means of controlling devices on activities of the PEs.